2021
DOI: 10.1111/jan.15114
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related potential traumatic events and job burnout among operating room nurses: Independent effect, cumulative risk, and latent class approaches

Abstract: Aims:The objective of this study is to explore and compare the strength of associations between work-related potential traumatic events and burnout among operating room nurses based on three different approaches. Design:The study followed a multisite cross-sectional design.Methods: A stratified sampling method was conducted. Cities in the Shandong Province were divided into four groups, and two tertiary hospitals were randomly selected from all tertiary hospitals in cities of each group. A total of 361 eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Alyssa A. Welch, MD  Brendon M. Esquibel, MD  Kohei A. Osterloth, BS  Kara J. Kallies, MS  Alec J. Fitzsimmons, MPH  Christine J. Waller, MD, FACS (Dimou et al, 2016;Guest et al, 2011, Lee et al, 2021Wang et al, 2021). Indeed, it may be one of the many factors contributing to trauma surgeons having the highest rates of burnout among surgical subspecialties, a rate some have reported to be over 50% (Balch et al, 2011;Dimou et al, 2016).…”
Section: Trauma and Death In The Emergency Department: A Time To Paus...mentioning
confidence: 99%
See 1 more Smart Citation
“…Alyssa A. Welch, MD  Brendon M. Esquibel, MD  Kohei A. Osterloth, BS  Kara J. Kallies, MS  Alec J. Fitzsimmons, MPH  Christine J. Waller, MD, FACS (Dimou et al, 2016;Guest et al, 2011, Lee et al, 2021Wang et al, 2021). Indeed, it may be one of the many factors contributing to trauma surgeons having the highest rates of burnout among surgical subspecialties, a rate some have reported to be over 50% (Balch et al, 2011;Dimou et al, 2016).…”
Section: Trauma and Death In The Emergency Department: A Time To Paus...mentioning
confidence: 99%
“…This number increases to over 246,000 when deaths due to violence-related injuries are included. Several studies have shown that witnessing patient death is one of the factors that have been associated with health care worker burnout (Dimou et al, 2016; Guest et al, 2011,Lee et al, 2021; Wang et al, 2021). Indeed, it may be one of the many factors contributing to trauma surgeons having the highest rates of burnout among surgical subspecialties, a rate some have reported to be over 50% (Balch et al, 2011; Dimou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, they have to provide continuous service and be highly concentrated throughout the procedures to ensure patient safety, in lest of the occurrence of adverse events (Li et al, 2022). Meanwhile, they are at high risk for biological, accidental, and chemical occupational exposures due to their direct contact with patients' blood and body fluids, as well as exhaust gases produced during operations (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%